Potential Inaccuracies in Chloride Measurements in Patients with Severe Metabolic Acidosis. (12th June 2012) - Makiishi, Tetsuya; Nishimura, Naomasa; Yoshioka, Keiko; Yamamoto, Shinya; Mitsuhashi, Ryuichi; Maeda, Sayako; Konishi, Takashi; Hirose, Kunihiko
Abstract : Background . To address the cause(s) of the significant differences in chloride (Cl - ) concentrations between point-of-care blood gas analyzers and central laboratory analyzers. Methods . Cl - concentrations measured simultaneously by a blood gas analyzer (ABL800 FLEX) and a central laboratory analyzer (Hitachi7600) were collected in patients with severe acidemia (pH < 7.20 ) (n = 32 ) and were examined for correlations between differences in Cl - and factors associated with the acid-base status. Cl - concentrations were measured with both analyzers for samples with different concentrations of lactate, inorganic phosphate, or bicarbonate (HCO 3       − ). Results . The differences in Cl - concentrations were correlated with HCO 3       − concentrations (r = 0.72, P < 0.0001 ) and anion gap (r = 0.69, P < 0.0001 ). Only the addition of HCO 3       − proportionately increased Cl - levels measured by a Hitachi7600, but it did not affect those measured by an ABL800FLEX. Conclusion . Cl - measurements with some analyzers may be influenced by HCO 3       − concentrations, which could result in the observed discrepancies.